Internet in the intermediation role of travel agents: The Portuguese case - Loureiro, S.; Ferreira, E.S.; Lopes, R. (MAG Scholar® Global Business Marketing and Tourism Conference 2015 Proceedings: Travel, discover, marketing, 2015)
This article attempts to assess the impact that Internet has in the intermediation of travel agencies operating in Portugal. Firstly, the study discusses theoretical concepts related to the topic such as: tourism, internet, characterization of tourism distribution, disintermediation, reintermediation and new integrated management systems for travel agents. Then, a questionnaire was developed which resulted in 125 valid responses. The data analysis showed that travel agencies are committed to a new type of intermediation based on new technologies, using new technology platforms to distribute their tourism products and services and to adopt new business models. The study concludes that, only this way, organisations will achieve sustainable growth.